Re-examining the holocaust through literature - Kluge, Aukje; Williams, Benn E. (Cambridge Scholars Pub., 2009)
In the late 1980s, Holocaust literature emerged as a provocative, but poorly defined, scholarly field. The essays in this volume reflect the increasingly international and pluridisciplinary nature of this scholarship and the widening of the definition of Holocaust literature to include comic books, fiction, film, and poetry, as well as the more traditional diaries, memoirs, and journals. Ten contributors from four countries engage issues of authenticity, evangelicalism, morality, representati ...